 #jsDisabledContent { display:none; } My Account | Register | Help Flag as Inappropriate This article will be permanently flagged as inappropriate and made unaccessible to everyone. Are you certain this article is inappropriate?          Excessive Violence          Sexual Content          Political / Social Email this Article Email Address:

# Free entropy

Article Id: WHEBN0004064439
Reproduction Date:

 Title: Free entropy Author: World Heritage Encyclopedia Language: English Subject: Collection: Publisher: World Heritage Encyclopedia Publication Date:

### Free entropy

A thermodynamic free entropy is an entropic thermodynamic potential analogous to the free energy. Also known as a Massieu, Planck, or Massieu–Planck potentials (or functions), or (rarely) free information. In statistical mechanics, free entropies frequently appear as the logarithm of a partition function. The Onsager reciprocal relations in particular, are developed in terms of entropic potentials. In mathematics, free entropy means something quite different: it is a generalization of entropy defined in the subject of free probability.

A free entropy is generated by a Legendre transform of the entropy. The different potentials correspond to different constraints to which the system may be subjected.

## Examples

The most common examples are:

 Name Function Alt. function Natural variables Entropy S = \frac {1}{T} U + \frac {P}{T} V - \sum_{i=1}^s \frac {\mu_i}{T} N_i \, ~~~~~U,V,\{N_i\}\, Massieu potential \ Helmholtz free entropy \Phi =S-\frac{1}{T} U = - \frac {A}{T} ~~~~~\frac {1}{T},V,\{N_i\}\, Planck potential \ Gibbs free entropy \Xi=\Phi -\frac{P}{T} V = - \frac{G}{T} ~~~~~\frac{1}{T},\frac{P}{T},\{N_i\}\,
where

Note that the use of the terms "Massieu" and "Planck" for explicit Massieu-Planck potentials are somewhat obscure and ambiguous. In particular "Planck potential" has alternative meanings. The most standard notation for an entropic potential is \psi, used by both Planck and Schrödinger. (Note that Gibbs used \psi to denote the free energy.) Free entropies where invented by French engineer Francois Massieu in 1869, and actually predate Gibbs's free energy (1875).

## Dependence of the potentials on the natural variables

### Entropy

S = S(U,V,\{N_i\})

By the definition of a total differential,

d S = \frac {\partial S} {\partial U} d U + \frac {\partial S} {\partial V} d V + \sum_{i=1}^s \frac {\partial S} {\partial N_i} d N_i.

From the equations of state,

d S = \frac{1}{T}dU+\frac{P}{T}dV + \sum_{i=1}^s (- \frac{\mu_i}{T}) d N_i.

The differentials in the above equation are all of extensive variables, so they may be integrated to yield

S = \frac{U}{T}+\frac{p V}{T} + \sum_{i=1}^s (- \frac{\mu_i N}{T}).

### Massieu potential / Helmholtz free entropy

\Phi = S - \frac {U}{T}
\Phi = \frac{U}{T}+\frac{P V}{T} + \sum_{i=1}^s (- \frac{\mu_i N}{T}) - \frac {U}{T}
\Phi = \frac{P V}{T} + \sum_{i=1}^s (- \frac{\mu_i N}{T})

Starting over at the definition of \Phi and taking the total differential, we have via a Legendre transform (and the chain rule)

d \Phi = d S - \frac {1} {T} dU - U d \frac {1} {T},
d \Phi = \frac{1}{T}dU+\frac{P}{T}dV + \sum_{i=1}^s (- \frac{\mu_i}{T}) d N_i - \frac {1} {T} dU - U d \frac {1} {T},
d \Phi = - U d \frac {1} {T}+\frac{P}{T}dV + \sum_{i=1}^s (- \frac{\mu_i}{T}) d N_i.

The above differentials are not all of extensive variables, so the equation may not be directly integrated. From d \Phi we see that

\Phi = \Phi(\frac {1}{T},V,\{N_i\}).

If reciprocal variables are not desired,:222

d \Phi = d S - \frac {T d U - U d T} {T^2},
d \Phi = d S - \frac {1} {T} d U + \frac {U} {T^2} d T,
d \Phi = \frac{1}{T}dU+\frac{P}{T}dV + \sum_{i=1}^s (- \frac{\mu_i}{T}) d N_i - \frac {1} {T} d U + \frac {U} {T^2} d T,
d \Phi = \frac {U} {T^2} d T + \frac{P}{T}dV + \sum_{i=1}^s (- \frac{\mu_i}{T}) d N_i,
\Phi = \Phi(T,V,\{N_i\}).

### Planck potential / Gibbs free entropy

\Xi = \Phi -\frac{P V}{T}
\Xi = \frac{P V}{T} + \sum_{i=1}^s (- \frac{\mu_i N}{T}) -\frac{P V}{T}
\Xi = \sum_{i=1}^s (- \frac{\mu_i N}{T})

Starting over at the definition of \Xi and taking the total differential, we have via a Legendre transform (and the chain rule)

d \Xi = d \Phi - \frac{P}{T} d V - V d \frac{P}{T}
d \Xi = - U d \frac {1} {T} + \frac{P}{T}dV + \sum_{i=1}^s (- \frac{\mu_i}{T}) d N_i - \frac{P}{T} d V - V d \frac{P}{T}
d \Xi = - U d \frac {1} {T} - V d \frac{P}{T} + \sum_{i=1}^s (- \frac{\mu_i}{T}) d N_i.

The above differentials are not all of extensive variables, so the equation may not be directly integrated. From d \Xi we see that

\Xi = \Xi(\frac {1}{T},\frac {P}{T},\{N_i\}).

If reciprocal variables are not desired,:222

d \Xi = d \Phi - \frac{T (P d V + V d P) - P V d T}{T^2},
d \Xi = d \Phi - \frac{P}{T} d V - \frac {V}{T} d P + \frac {P V}{T^2} d T,
d \Xi = \frac {U} {T^2} d T + \frac{P}{T}dV + \sum_{i=1}^s (- \frac{\mu_i}{T}) d N_i - \frac{P}{T} d V - \frac {V}{T} d P + \frac {P V}{T^2} d T,
d \Xi = \frac {U + P V} {T^2} d T - \frac {V}{T} d P + \sum_{i=1}^s (- \frac{\mu_i}{T}) d N_i,
\Xi = \Xi(T,P,\{N_i\}).